Evaluation of Nickel Ion Release from Orthodontic Wires in Different Types of Artificial Saliva - Amer. A. Taqa; Wafaa Gh. Fathi; Ruba J. Mohammed (University of Mosul, College of Dentistry, 2014)
Aims: To evaluate the amount of nickel ion release from stainless steel orthodontic wires in different artificial saliva and in different time periods. Materials and Methods: This study included six different commercial stainless steel orthodontic wires with different diameters. They were immersed in deionized water (control) and three different artificial saliva, the immersion periods included 7, 14, and 30 days. A graphite-furnace atomic absorption spectrometer (AAS) was used to determine the amount of nickel ions release. Results: The statistical analysis showed that there is a highly significance in the release of nickel ions for all types of wire except wires 0.18, and 0.16 x 0.22 which gave non-significant 2.45 and 1.37 respectively, and the time period of immersion had no significant effect in all types of wire. Conclusions: The release of nickel ions was influenced by the types of wire and the surface areas that in contact with immersion in solution, in addition to the composition of the orthodontic wires, but this were not proportional to the content of metal in the wire.